Plenary studies in the conditions of art education - E.H. Semenko (Academy of Cognitive and Natural Sciences, 2009)
This article и devoted to some problems of the open-air painting. Special attention is paid to brief sketches as a methodical basis for performing king sketches and pictures in particular.